A Comparison of Observational Models in Learning Various Tasks - mahtab arabi; Abdollah Ghasemi; Seyed Mohammad Kazem Vaez Mousavi (University of Tehran, 2017)
The aim of this study was to compare observational models in learning motor task of receiving a volleyball ball and motor-cognitive task of juggling with 3 balls. The participants were 80 female students aged between 19 and 25. 40 subjects participated in each task. Participants were divided into 4 groups: novice model observation, expert, mixed and physical practice. All observational groups watched their own model via video tapes. In this study, some acquisition phases, retention and transfer tests were carried out in all two tasks. In acquisition phase, data were analyzed with ANOVA with repeated measures and in retention and transfer tests one-way ANOVA test and proper post hoc tests were used (P<0.05). In the acquisition phase, observation of expert-novice model in the motor task was better than the other groups but this predominance was not significant. But in the retention and transfer tests, observation of this model had a significant predominance. In the cognitive-motor task, the observation of novice model was better than the other groups during the acquisition phase, retention and transfer tests but this predominance was not significant in the transfer test. Finally,based on the results of the present study, it is suggested that various modeling methods should be used to learn different tasks.